A national study on conditional survival, excess mortality and second cancer after high dose therapy with autologous stem cell transplantation for non‐Hodgkin lymphoma. (23rd February 2016) - Smeland, Knut B.; Kiserud, Cecilie E.; Lauritzsen, Grete F.; Blystad, Anne K.; Fagerli, Unn‐Merete; Falk, Ragnhild S.; Fluge, Øystein; Fosså, Alexander; Kolstad, Arne; Loge, Jon H.; Maisenhölder, Martin; Østenstad, Bjørn; et al.
Summary: This national population‐based study aimed to investigate conditional survival and standardized mortality ratios (SMR) after high‐dose therapy with autologous stem‐cell transplantation (HDT‐ASCT) for non‐Hodgkin lymphoma (NHL), and to analyse cause of death, relapses and second malignancies. All patients ≥18 years treated with HDT‐ASCT for NHL in Norway between 1987 and 2008 were included ( n  = 578). Information from the Cause of Death Registry and Cancer Registry of Norway were linked with clinical data. The 5‐, 10‐ and 20‐year overall survival was 61% (95% confidence interval [CI] 56–64%), 52% (95%CI 48–56%) and 45% (95%CI 40–50%), respectively. The 5‐year survival conditional on having survived 2, 5 and 10 years after HDT‐ASCT was 81%, 86% and 93%. SMRs were 12·3 (95%CI 11·0–13·9), 4·9 (95%CI 4·1–5·9), 2·4 (95%CI 1·8–3·2) and 1·0 (95%CI 0·6–1·8) for the entire cohort and for patients having survived 2, 5 and 10 years after HDT‐ASCT respectively. Of the 281 deaths observed, 77% were relapse‐related. Treatment‐related mortality was 3·6%. The 10‐year cumulative incidence of second malignancies was 7·9% and standardized incidence ratio was 2·0 (95%CI 1·5–2·6). NHL patients treated with HDT‐ASCT were at increased risk of second cancer and premature death. The mortality was still elevated at 5 years, but after 10 years mortality equalled that of the general population.